Treating Chronic Energy Deficiency in Pregnant Women with NUTATEL - Komariyah; Isahayati; Junika Isti; Endaryati; Yeti Rosmawati; Siauta, Jenny Anna (Rajaki of Tulip Medika Publisher, 2025)
Based on the preliminary survey results, TPMB JUNIKA ISTI is located at Jl. Lintas Desa Terulung No. 85, Manna District, South Bengkulu Regency, Bengkulu Province, South Jakarta City, TPMB Junika Isti. Based on data obtained from the Patient Visit Report, it was obtained that pregnant women visited TPMB. JUNIKA ISTI in the last 3 months an average of 82 visits, out of 82 pregnant women, there were 7 visits of KEK pregnant women, namely in September as many as 2 people, in October as many as 3 people and in November as many as 2 people. Of the 7 KEK pregnant women, 4 people were too young. KEK is a condition where a person suffers from an imbalance in nutritional intake (energy and protein) that lasts for years. Pregnant women who experience KEK will have problems during pregnancy, childbirth and postpartum. In addition, it will also have an impact on fetal development. The government has made efforts to help reduce the incidence of KEK in pregnant women by providing additional food regularly to pregnant women, but these efforts have not been able to achieve the expected target. The purpose of implementing community service is to increase the knowledge of pregnant women, cadres, and community leaders about the impacts caused by pregnant women experiencing KEK and how to handle it. The implementation of the intervention was carried out by pre-test and post-test assessments to see the effectiveness of the counseling provided. The evaluation results showed that there was an increase in knowledge in pregnant women with an average value of the pre-test results of 42 and the post-test results of 82. So it can be concluded that pregnant women understand the impacts caused by KEK during pregnancy. We advise pregnant women to be able to meet balanced nutritional intake during pregnancy by consuming foods that are high in calories and protein, by the innovation provided, namely NUTATEL (Carrot Egg Tofu Nuggets)